2018
DOI: 10.1186/s12876-018-0877-9
|View full text |Cite
|
Sign up to set email alerts
|

Low lymphocyte count and high monocyte count predicts poor prognosis of gastric cancer

Abstract: BackgroundExisting data about the prognostic value of absolute count of blood cells in gastric cancer was limited. Thus, the present study aims to investigate the prognostic value of absolute count of white blood cell (WBC), neutrophil, lymphocyte, monocyte and platelet in gastric cancer patients.MethodsFrom September 2008 to March 2015, 3243 patients treated with radical gastrectomy were enrolled in the present study. Clinicopathological characteristics were recorded. The prognostic value of blood test in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 34 publications
4
85
0
1
Order By: Relevance
“…Tumour inflammatory microenvironments are complex and dynamic, involving crosstalk between various immune cells and tumour cells. Inflammatory prognostic scores such as the NLR, PLR, and LMR calculated using immune cellrelated values have shown promise in various tumour types [16][17][18][19]. In addition, the efficacy of the SIRI has been reported in limited types of cancer, such as liver [20], pancreatic [3], gastric [4], and nasopharyngeal [5] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour inflammatory microenvironments are complex and dynamic, involving crosstalk between various immune cells and tumour cells. Inflammatory prognostic scores such as the NLR, PLR, and LMR calculated using immune cellrelated values have shown promise in various tumour types [16][17][18][19]. In addition, the efficacy of the SIRI has been reported in limited types of cancer, such as liver [20], pancreatic [3], gastric [4], and nasopharyngeal [5] cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes play a prominent role in tumor-related immunology and lymphopenia has been reported to be associated with poor prognosis in many solid tumors including NSCLC, melanoma, gastric-, breast-, and colon cancers. 12,35,36 Cho et al investigated the effects of lymphopenia on OS and progression-free survival (PFS) in immunotherapy treated patients and found that lymphopenia within 0-2 months from the initiation of immunotherapy also showed significantly inferior OS and PFS. 12 Accordingly, changes in ALC should be carefully evaluated in patients who are future candidates for immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high numbers/percentages of circulating monocytes indicate poor clinical prognosis in cancer 13 , suggesting that the level of monocytes in blood may in uence tumor development. In line with this hypothesis, it was recently shown that the peripheral count of monocytes was associated with the density of tumor-associated macrophages in colorectal cancer 14,15 . During in ammation, metabolic and epigenetic rewiring has been identi ed as important mechanisms of monocyte, and more generally myeloid cell, production and function 16 .…”
Section: Introductionmentioning
confidence: 60%